Clinical Results of Bioabsorbable Pin Fixation Relative to the Bone Condition for Osteochondral Lesion of the Talus. (December 2019) - Nakasa, Tomoyuki; Ikuta, Yasunari; Ota, Yuki; Kanemitsu, Munekazu; Adachi, Nobuo
Background: Fixation of an osteochondral lesion of the talus (OLT) can restore the natural congruency of the joint surface with hyaline cartilage. In this procedure, the bone condition of the osteochondral fragment is important for stabilizing the lesion, and it may affect clinical outcomes. The aim of this study was to explore the influence of the fragment's bone condition on clinical outcomes. Methods: Eighteen ankles in 17 patients with a mean age of 20.1 years, which had undergone fixation of an OLT using bioabsorbable pins, were included. Based on the fragment's bone condition on preoperative computed tomography scans, ankles were divided into 3 groups: normal, segmentation, and absorption. The American Orthopaedic Foot & Ankle Society (AOFAS) scale and magnetic resonance imaging (MRI) findings were evaluated both pre- and postoperatively. Second-look arthroscopic findings were evaluated in 15 ankles and were compared with biopsy specimens from the initial surgery. Results: The AOFAS scale significantly improved at the final follow-up in all groups with no significant differences among the 3 groups. MRI at 1 year showed good bone incorporation and a congruent cartilage surface in all groups, but the bone marrow lesion in the absorption group was significantly larger than that in the other groups. In second-look arthroscopy, all ankles showed stable and near-normal cartilage. There was no significant correlation between arthroscopic and histological findings. Conclusion: We found that fixation can be considered when there is a good cartilage surface on a large OLT, even if bone absorption in the fragment exists. Level of Evidence: Level III, comparative study.